2020
DOI: 10.3390/vetsci7030140
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sources of Potential Bias When Using Online Survey Data to Explore Horse Training, Management, and Behaviour: A Systematic Literature Review

Abstract: Owner-reported behavioural observations form an essential part of the veterinarians’ diagnosis and treatment plan. The way we train and manage horses affects their behaviour and, in turn, their health and welfare. Current horse training and management practices are largely driven by traditional techniques and longstanding methodologies. These approaches generally lack an evidence base for evaluation purposes. The absence of evidence and evaluation contributes to the persistent use of risky practices and this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…However, the horses in their studies were individually observed and scored for boldness by the experimenters rather than from scores based on owner-reported observations, as the current study did. The use of owner-reported observations may be considered a more accurate representation of boldness in horses than one-off tests results [52]. This may explain the difference among the studies.…”
Section: Boldnessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the horses in their studies were individually observed and scored for boldness by the experimenters rather than from scores based on owner-reported observations, as the current study did. The use of owner-reported observations may be considered a more accurate representation of boldness in horses than one-off tests results [52]. This may explain the difference among the studies.…”
Section: Boldnessmentioning
confidence: 99%
“…In previous studies, when asked to recall events within a three-to six-month period, respondents scored a three-out-of-five for recall, whereas respondents reporting events within a week of their occurrence scored a five-out-of-five for recall [54,[74][75][76][77][78][79][80]. Previous investigations into the potential sources of bias inherent in equine behavioural data collection [52] revealed three main sources: recall, confirmation and sampling bias. As a validated instrument [46], E-BARQ attempts to minimise their impact.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, in asking whether breeders took responsibility for various aspect of their puppies' future, we may have overlooked the prospect that some respondent may have interpreted this as total responsibility, whereas others may have interpreted it as partial responsibility. Other possible sources of bias with online surveys of animal owners, including the prospect that participants may sanitise their responses have been discussed elsewhere [27].…”
Section: Limitationsmentioning
confidence: 99%
“…The current study has some limitations. Although the sample size for this study ( n = 2445) was relatively large, the methods of sampling were not optimal for generalisability of the findings, with some unavoidable biases potentially introduced by online sampling [ 62 ]. Additionally, few of the current participants were male (9%), though this female bias replicates demographic imbalances reported in similar studies [ 4 ], so the current results are likely comparable with those in the existing companion animal literature.…”
Section: Discussionmentioning
confidence: 99%